HETEROSIS AND COMBINING ABILITY IN SAFFLOWER (CARTHAMUS TINCTORIUS L.) GERMPLASM LINES - JHAJHARIA, SUNITA; CHOUDHARY, PRATIBHA; JHAJHARIA, ARUN (The Bioscan, 2013)
Improvement of seed yield and oil content in safflower (Carthamus tinctorius L.) as an oilseed crop is the main objective of its breeding programs. However, little genetic information is available for these traits. GCA and SCA mean square were significant with preponderance of GCA effects for all the characters in individual environments and in pooled analysis except for primary branches per plant, biological yield and oil content in pooled analysis. The germplasm lines GMU 7359 and GMU 5394 were good general combiner for many of the important characters, specially seed yield, total capitula per plant, 100 seed weight, biological yield, harvest index and oil content in almost all the four analysis. The germplasm GMU 3806, GMU 5267 and GMU 5394 were good general combiners for earliness, short plant stature and primary branches per plant also. For SCA effects the best crosses identified in pooled analysis were GMU 5815 x GMU 217and GMU 5815 x GMU 217 for seed yield. These crosses also recorded high heterotic effect, high per se performance and stability over varied environments. They also depicted high SCA effect and high heterosis for effective capitula per plant, 100 seed weight, biological yield and oil content. For early flowering the cross GMU 5394 x GMU 196 and GMU 3806 x GMU 217 exhibited high SCA effect GMU 5394 x GMU 196, GMU 5712 x GMU 7359 and GMU 5815 x GMU 217 recorded maximum negative SCA effects for days to maturity. Hybrid GMU 5267 x GMU 5815, GMU 3714 x GMU 7359 and GMU 5394 x GMU 217 exhibited maximum SCA effect for oil content.